Performance evaluation of a mercury-steam combined-energy-generation system (MES) - Gonca, Guven; Sahin, Bahri (WILEY, 2019)
In this study, exergy and thermo-ecology-based performance analyses of a mercury-steam combined-energy-generation system are comprehensively presented. Performance characteristics such as net-power output, net-power density, exergy efficiency, exergy destruction, and ecological coefficient of performance have been obtained by developing a novel numerical model. The impacts of the pressures of open feed water heater and steam turbines, temperatures of mercury boiler, and mercury turbines on the performance characteristics have been investigated. The results indicated that the performance characteristics of the system have been remarkably affected by the pressure and temperature variations of the system components.
Keywords: binary cycles; combined-power-generation system; ECOP; parametric performance evaluation; steam cycle; thermo-ecology; ORGANIC RANKINE-CYCLE; OXIDE FUEL-CELL; SUPERHEATED STEAM; COMBINED HEAT; POWER-SYSTEM; THERMODYNAMIC ANALYSIS; EXERGETIC ANALYSIS; OPTIMIZATION; TURBINE; PLANT; Energy & Fuels; Nuclear Science & Technology